All unquiet things - Jarzab, Anna. (New York : Delacorte Press, 2010)
After the death of his ex-girlfriend Carly, northern California high school student Neily joins forces with Carly's cousin Audrey to try to solve her murder.
Keywords: Murder -- Fiction; Social classes -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Detective and mystery stories; California, Northern -- Fiction; Mystery fiction